An extreme bounds analysis of the impact of the COVID-19 outbreak on cryptocurrencies. (30th September 2021) - Temkeng, Serge Djoudji; Fofack, Achille Dargaud
The aim of this paper is to find out if the COVID-19 outbreak in the USA has a robust impact on the prices of cryptocurrencies. Inspired by the literature related to the determinants of cryptocurrency prices and based on data availability, six potential determinants of cryptocurrency prices and five proxies for the COVID-19 outbreak were selected. The impact of the COVID-19 outbreak was tested using two approaches of extreme bounds analysis and the robustness of our findings was further checked with different cryptocurrencies (Bitcoin, Ethereum, Litecoin and Bitcoin Cash). Our results show that new deaths from the COVID-19 have a robust positive impact on the price of cryptocurrencies while the impact of new confirmed cases, total cases, and total deaths is not robust. In line with previous studies, it is also found that economic uncertainty, stock, gold, and oil prices are robust determinants of the value of cryptocurrencies.